TECHNOLOGY OF PRODUCTION OF CERAMIC MATERIALS AND ITS VALUE TODAY - Shodiev Sadir Nematovich; Duskaraev Nortaylok Abduganievich; Shodiev Nematjon Sadirovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses the extraction, types, application, electrical conductivity and other properties of ceramics, water and gas permeability of ceramics, porcelain, earthenware and other types of fine ceramics, glazed glazing and reheating to 1000-1400.